Development and Evaluation of Matrix Type Transdermal Patches of Torasemide - Kumar, Ashish; Kumar, Kapil (Journal of Drug Delivery and Therapeutics, 2020)
TDDS manufacture has numerous benefits over other routes like oral delivery. It avoids limitations linked with g.i.t. absorption, enzyme effect, interaction with drug and food. This route is suitable when patient is suffering from vomiting and diarrhea. Torasemide is a loop diuretic; it comes under category of sulfonyl urea. It is prescribed in the treatment of edema, CHF, and hypertension.  Whenever it is used by oral route, it is associated with many side effects like vomiting, nausea, anorexia, and increased appetite. All transdermal patches were transparent and free from any particle. Release profile of twelve batches of Torasemide was done by the means of Franz cell for 7 hrs. Maximum release was shown by MTP6 (71.28±0.19) and least in formulations of batch code MTP7(24.47±0.04). In-vitro release data were plotted in 2 different models i.e. first and Korsemeyer peppas. It was observed that release was governed by the diffusion process. On basis of different properties MTP1 batch was found to be optimum. Study concludes that by the means of patches Torasemide can be administered efficiently.Keywords: Torasemide, transdermal patches, HPMC, in-vitro release, stability studies, TDDS.